2012
DOI: 10.1002/pon.3139
|View full text |Cite
|
Sign up to set email alerts
|

Individual and family characteristics associated with BRCA1/2 genetic testing in high‐risk families

Abstract: Findings suggest that both individual and family characteristics are associated with the decision to obtain genetic testing for hereditary breast cancer; hence, there is a need for interventions that foster a supportive family environment for patients and their high-risk relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…The study was guided by the integration of the theory of stress and coping with the theory of family systems in genetic illness applied to families with hereditary breast cancer risk . Stress occurs when primary appraisals of a health problem threaten one's well‐being .…”
Section: Introductionmentioning
confidence: 99%
“…The study was guided by the integration of the theory of stress and coping with the theory of family systems in genetic illness applied to families with hereditary breast cancer risk . Stress occurs when primary appraisals of a health problem threaten one's well‐being .…”
Section: Introductionmentioning
confidence: 99%
“…Although we have successfully used the same recruitment method (patient recruiting relative) in our prior studies targeting women completing genetic testing and young breast cancer survivors [11,15,80], the usability and feasibility study indicated that recruitment of mutation carriers and relatives for a family-based intervention requires personal contact and follow-up phone calls. The pre-post pilot study indicated that personal contact with mutation carriers is necessary first, to assess their eligibility to participate in the Family Gene Toolkit© (i.e., confirmed BRCA mutation, not all relatives have been tested) and second, to prepare them how to broach family participation in an intervention study with their relative, and help minimize relative refusal rate.…”
Section: Enhancing Recruitment: Personal Contact To Mutation Carriersmentioning
confidence: 99%
“…(Figure 1). findings from a descriptive study with 168 at-risk families [11,62]; a meta-analysis of interventions targeting cancer patients and their family caregivers [63]; feedback from a psychologist, expert in decision-making for genetic testing, not involved in the development in the intervention; and feedback from two BRCA families (two female carriers and two female relatives). The intervention prototype targets family dyads consisting of a female mutation carrier and a female close biological relative.…”
Section: Development Of the Family Gene Toolkit©mentioning
confidence: 99%
See 2 more Smart Citations